Development of Project Based Ethno-STEM Online Learning Module to Increase Interpersonal Literacy and Learning Out-come - Imam Setiawan; Sudarmin Sudarmin; Partaya Partaya (Journal of Innovative Science Education, 2023)
Interpersonal skills are ability to understand sociocultural phenomena which include aspects of communication, appreciation, tolerance, caring, empathy, and being able to work with others and be able to adapt well in the surrounding environment. This is a very important provision that must be owned by every student. Purpose of this research is to develop learning media for brave science that examines local wisdom content to study the topic of food ingredients. This research was conducted at An-Nur Ungaran Middle School and several traditional food industry places around the student's residences. The research method used is R&D with the ADDIE model. This media was validated and declared appropriate by media experts and material experts, then applied in science learning. The data obtained from the readability test, and the N-Gain test from students. The results of the study show that 1) Ethno-STEM learning module can be developed using the ADDIE model and is declared feasible to be applied in learning; 2) Ethno-STEM learning module can be developed to have good readability results, namely at a score of 61.4%; 3) Using of this Ethno-STEM module can improve interpersonal literacy and learning outcomes with N-gain values of 0.31 and 0.33, respectively.